Change in estimated glomerular filtration rate and outcomes in chronic kidney disease. Issue 3 (May 2016) - Ferguson, Thomas W.; Komenda, Paul; Tangri, Navdeep
Abstract : Purpose of review: Estimated glomerular filtration rate (eGFR) is important in the diagnosis and prognostication of chronic kidney disease (CKD). The current standards for CKD progression in clinical trials are kidney failure and the doubling of serum creatinine (∼57% decline in eGFR). These endpoints have limitations as they are only applicable to patients with later stages of CKD and often require large sample sizes to achieve adequate power. Recent findings: Lesser declines in eGFR (30% and 40%) have been evaluated as potential endpoints in recent studies. These endpoints are more common and show a strong association with the risk of end-stage renal disease and mortality. These findings have been shown to be consistent across different causes of CKD and for different interventions. A particular limitation of reduced thresholds is an elevated risk of type I errors in the presence of acute treatment effects, particularly with a 30% eGFR decline cut off. Summary: Surrogate endpoints for kidney failure and mortality are needed in clinical trials to allow for the reasonable management of timelines and resources, and the achievement of adequate sample sizes. Lesser eGFR decline thresholds should be considered to aid in the design and conduct of more randomized controlled trials in nephrology.